Awareness Among Potential Advertising Designer Regarding ITV Advertising - Che Omar, Azizah; ., . (International Journal of Engineering and Technology, 2018)
Conceptual Design Model of Interactive Television Advertising Towards Influencing Impulse Purchase Tendency (iTVAdIP) is proposed to provide guideline for advertising designers to develop iTV advertisements which embed elements that are perceived could influence impulse purchase tendency. Previous literature studied on the factors of impulse purchase in different advertising mediums like website, mobile, traditional retail store and traditional television. However, none of the impulse purchase model is dedicated towards influencing impulse purchase tendency for interactive TV advertising. Therefore, this study focuses on the awareness among potential advertising designer regarding iTV advertising. A series of interviews were conducted involving 58 potential advertising designers. The results from interview are presented in this paper, indicating that majority of the respondents indicate that, there is a difference between advertising with interaction and without interaction elements where the advertising with interactive interaction elements could perceived influence more consumers in their purchasing tendency compared to advertising without interaction elements.Â Â